The Effect Of Brand Personality, Price Perception And Product Quality On Purchasing Decisions (Survey on Batik Deden Tasikmalaya Product Consumers) - Febriany, Rizka Nurhaliza; Pauzy, Depy Muhamad; Risana, Dudu (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
This purpose of this study to determine the effect of Brand Personality, Price Perception and Product Quality on Purchasing Decisions on Batik Deden Tasikmalaya Products (Survey on Batik Deden Tasikmalaya Product Consumers). The method used is a quantitative approach with a research sample of 100 consumer respondents of Batik Deden Tasikmalaya products. The data used are primary and secondary data. The analytical tool used in this research is multiple linear regression analysis using SPSS version 25. The results showed that simultaneously Brand Personality, Price Perception and Product Quality had a significant effect on Purchasing Decisions. Partially Brand Personality has no effect on Purchasing Decisions. Partially Price Perception has a significant effect on Purchasing Decisions. Partially Product Quality has a significant effect on Purchasing Decisions.